Liangfang Wenjing decoction regulates endoplasmic reticulum stress-mediated apoptosis to alleviate uterine microvascular injury in cold-stressed rats - Lv, Tianyuan; Hu, Yue; Ma, Xueyan; Feng, Liqun; Wang, Di; Song, Xiaodan; Xue, Sisi; Lu, Shuai; Cheng, Xiumei (Frontiers in Pharmacology, 2025)
BackgroundCold exposure can induce microvascular damage, which in turn contributes to various gynecological disorders. Liangfang Wenjing Decoction (LFWJD), a classical botanical drug prescription, has long been used to treat gynecological diseases caused by cold through improving microvascular injury. Nevertheless, its underlying therapeutic mechanism is still unclear. This study aimed to elucidate the effects of cold stress on uterine microvessels and to explore the pharmacological mechanisms through which LFWJD mitigates uterine microvascular injury.MethodsUPLC-MS/MS analysis was used to identify the major metabolites in LFWJD. A rat cold stress model was established using ice-water bath treatment, to investigate the mechanisms by which LFWJD ameliorates uterine microvascular injury. The study assessed several parameters, including the estrous cycle of rats, hemorheology indices, real-time blood flow in the auricle and uterine surfaces, and uterine arterial hemodynamics. Uterine histopathology and ultrastructural changes in vascular endothelial cells were observed. Serum and uterine tissue endothelial factors were quantified by ELISA, while apoptosis in uterine and vascular endothelial cells was evaluated using TUNEL staining. Western blotting and immunofluorescence were performed to detect the expression of apoptosis-related proteins, endoplasmic reticulum stress (ERS) marker proteins, and proteins associated with the IRE1α/ASK1/JNK and IRE1α/XBP1s signaling pathways.ResultsTreatment with LFWJD for 21 days restored the estrous cycle in cold-stressed rats and improved uterine histopathology, as evidenced by an increased number of glands and thickening of the endometrium. LFWJD also enhanced blood perfusion in the auricle and uterine surface, regulated vascular endothelial factors (ET-1, NO, vWF, and TM), and repaired the ultrastructural integrity of endothelial cells. Moreover, it reduced apoptosis in uterine tissue and vascular endothelial cells by downregulating the expression of pro-apoptotic proteins (Bax, and cleaved caspase3) and ERS-related factors (GRP78, CHOP, XBP1s, p-IRE1α, p-ASK1, and p-JNK), while upregulating the anti-apoptotic protein Bcl-2 protein. Collectively, these pharmacological effects contributed to the alleviation of uterine microvascular injury in the uterus of cold-stressed rats.ConclusionLFWJD may exert its pharmacological effects by inhibiting the expression of ERS-related signaling pathway proteins and alleviating apoptosis, thereby improving uterine microvascular injury. This will provide an experimental foundation for the potential clinical application of LFWJD.